Mediastinal teratoma presenting with hemoptysis and pleuritis misdiagnosed as tuberculosis (empyema) - Jinrong Liu; Baolin Tian; Qi Zeng; Chenghao Chen; Chunju Zhou; Huimin Li; Yuelin Shen; Shunying Zhao (BMC, 2018)
Abstract Background Mediastinal teratoma is uncommon in children. It can be very difficult to diagnose especially in early stage. Rarely, teratoma may rupture into adjacent structures and lead to lung lesions or pleuritis. The main rarity of our reported cases was the dynamic imaging findings very similar to the developmental process of tuberculosis in patients 1 and 2, the pachypleuritis in patients 2 and 3, the extremely elevated inflammatory markers very similar to empyema in patient 3, and the extremely atypical tumor shape in all patients. Case presentation We present three pediatric patients presenting predominantly with recurrent hemoptysis and/or chest pain who were ultimately diagnosed with mediastinal teratoma containing pancreatic tissue. All three patients were initially suspected to have tuberculosis or empyema, and underwent relevant treatment, but without improvement. Patient 1 had left hilar enlargement, and subsequently an enlarging calcified cavity within high-density consolidation was identified. Patient 2 initially presented with right-sided pulmonary consolidation and pleuritis, and subsequently developed right lower lobe calcification, pleural thickening, and irregular soft tissue in the right inferior mediastinum. Patient 3 was initially found to have right lobe consolidation accompanied by a massive right-sided pleural effusion with extremely elevated inflammatory markers in serum and pleural effusion. The effusion later acquired heterogeneous density and appeared to become encapsulated. In patients 2 and 3, pleural biopsy identified fibrous tissue (with and without granuloma). Thoracotomy/thoracoscopy revealed mediastinal teratoma in each case, all of which were completely excised and the patients made uneventful recoveries. Histopathologic analysis revealed mature cystic-solid teratoma containing pancreatic tissue in all patients, and calcification in patients 1 and 2. Conclusions Clinicians should be mindful that mediastinal teratoma is a potential cause of hemoptysis, lung lesions and pleuritis. Calcification and pachypleuritis on chest imaging especially in patients without fever should be highly suspected of mediastinal teratoma. Pleural biopsy sometimes fails to assist in making a definitive diagnosis.